2019
DOI: 10.15241/nc.9.4.285
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Relational Predictors of Compassion Fatigue Among Counselors-in-Training

Abstract: This interview is the fourth in the Lifetime Achievement in Counseling Series at TPC that presents an annual interview with a seminal figure who has attained outstanding achievement in counseling over a career. I am honored to present the interview of Liliana Sznaidman, a professional counselor in North Carolina. Ms. Sznaidman is the second practitioner to be interviewed for this annual series. Ms. Sznaidman is a licensed professional counselor and licensed professional counselor supervisor with over 20 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…In addition, higher levels of social support, emotional intelligence, emotion management, and adaptive coping strategies were negatively correlated with compassion fatigue among health care professionals (Zeidner et al, 2013). Can and Watson's (2019) study of counselors-intraining found that higher levels of resilience and wellness were associated with lower levels of compassion fatigue. Other factors associated with lower levels of compassion fatigue include the practice of mindfulness (Constantine- Brown et al, 2017;Thompson et al, 2014); specialized trauma training (Sprang et al, 2007); higher levels of selfdifferentiation, professional self-esteem, and perceived marital quality (Finzi-Dottan & Kormosh, 2018); possessing a sense of coherence (Linley & Joseph, 2007) and use of an evidence-based therapy model (Craig & Sprang, 2010).…”
Section: Compassion Fatigue and Burnoutmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, higher levels of social support, emotional intelligence, emotion management, and adaptive coping strategies were negatively correlated with compassion fatigue among health care professionals (Zeidner et al, 2013). Can and Watson's (2019) study of counselors-intraining found that higher levels of resilience and wellness were associated with lower levels of compassion fatigue. Other factors associated with lower levels of compassion fatigue include the practice of mindfulness (Constantine- Brown et al, 2017;Thompson et al, 2014); specialized trauma training (Sprang et al, 2007); higher levels of selfdifferentiation, professional self-esteem, and perceived marital quality (Finzi-Dottan & Kormosh, 2018); possessing a sense of coherence (Linley & Joseph, 2007) and use of an evidence-based therapy model (Craig & Sprang, 2010).…”
Section: Compassion Fatigue and Burnoutmentioning
confidence: 96%
“…In contrast, the debilitating impact of compassion fatigue on mental health professionals has been well documented (Adams et al, 2006;Can & Watson, 2019;Martin-Cuellar, 2019;O'Brien & Haaga, 2015;Wagaman et al, 2015). Defined as a form of caregiver burnout developed by those who work with traumatized individuals (Figley, 2002), the construct of compassion fatigue incorporates two components.…”
mentioning
confidence: 99%
“…Neglecting one's self-care has been cited as a risk factor for developing compassion fatigue (Ray, Wong, White, & Heaslip, 2012), and like other professions, offsetting student-care with self-care can be a challenge for some (Can & Watson, 2019). Given that there has been a long-standing stigma that self-care is self-indulging or a personal luxury, it can prove challenging for some to make the paradigm shift (Carroll, Gilroy, & Murra, 1999).…”
Section: Risk Factors For Compassion Fatiguementioning
confidence: 99%
“…There is substantial evidence indicating that novice therapists are more susceptible to developing CF or vicarious trauma reactions. In particular, working with severely traumatized refugee patients poses risks for therapists in training (Can & Watson, 2019; Carmel & Friedlander, 2009; Craig & Sprang, 2010; Skovholt & Trotter-Mathison, 2011; Voss Horrell et al, 2011). Providing care for this population might invoke difficult emotions and traumatic reactions in a supervisee tapping into their dissociated self-states (see Bromberg, 2006), which might lead to CF and VT.…”
Section: Promoting Trauma-informed Approaches In Caring For Refugeesmentioning
confidence: 99%